Study on Acetylcholinesterase Inhibitory, Anti-inflammatory and Antioxidant Activities of Holarrhena antidysenterica Bark - Sunthorn Mukem (Prince of Songkla University, 2016)
Thesis (M.Sc., Herb Sciences)--Prince of Songkla University, 2011